2008
DOI: 10.1093/schbul/sbn068
|View full text |Cite
|
Sign up to set email alerts
|

Reward Processing in Schizophrenia: A Deficit in the Representation of Value

Abstract: Patients with schizophrenia demonstrate deficits in motivation and learning that suggest impairment in different aspects of the reward system. In this article, we present the results of 8 converging experiments that address subjective reward experience, the impact of rewards on decision making, and the role of rewards in guiding both rapid and long-term learning. All experiments compared the performance of stably treated outpatients with schizophrenia and demographically matched healthy volunteers. Results to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
408
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(446 citation statements)
references
References 77 publications
31
408
2
5
Order By: Relevance
“…These findings support the premise that these mice exhibit impaired anticipation of reward. Such impaired probabilistic (rewardassociative) learning has also been linked to anhedonia and negative symptoms in schizophrenia (Dowd and Barch, 2010;Waltz and Gold, 2007), via impaired reward anticipation Gold et al, 2008). However, these deficits could still be linked to impaired cognition, given that probabilistic learning was suggested by the CNTRICS initiative to measure long-term relational memory (Armstrong et al, 2012;Ragland et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support the premise that these mice exhibit impaired anticipation of reward. Such impaired probabilistic (rewardassociative) learning has also been linked to anhedonia and negative symptoms in schizophrenia (Dowd and Barch, 2010;Waltz and Gold, 2007), via impaired reward anticipation Gold et al, 2008). However, these deficits could still be linked to impaired cognition, given that probabilistic learning was suggested by the CNTRICS initiative to measure long-term relational memory (Armstrong et al, 2012;Ragland et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…RDoC domains such as cognitive control can be measured using the 5-Choice Continuous Performance Test (5C-CPT) Young et al, 2009Young et al, , 2013a, in which patients with schizophrenia (Young et al, 2013a) and bipolar mania (Young, Geyer, Minassian and Perry; unpublished observations) exhibit deficits. Positive valence, specifically the subconstruct of preference-based decision making of approach motivation, can be measured using a probabilistic learning task (Amitai et al, 2013;Bari et al, 2010), in which schizophrenia patients exhibit deficits (Armstrong et al, 2012;Gold et al, 2008;Ragland et al, 2012a;Waltz et al, 2011). The subconstruct of effort valuation can be measured using the progressive ratio breakpoint paradigm (PRBP; Bensadoun et al, 2004; that is also impaired in schizophrenia patients (Ellenbroek and Cools, 2000;Wolf et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Arbib and Mundhenk (2005) extended this proposal and suggested that dysfunctions in the mirror neuron system may also contribute to deficits in self-monitoring in schizophrenia. Pathological conditions that express deficits in social cognition and social functioning have also been found to have underlying abnormalities in reward processing, including ASDs (Dichter, Richey, Rittenberg, Sabatino, & Bodfish, 2012;Scott-Van Zeeland, Dapretto, Ghahremani, Poldrack, & Bookheimer, 2010) and schizophrenia (Gold, Waltz, Prentice, Morris, & Heerey, 2008). It may be the case that in such clinical populations, patients may have abnormal experiences of reward and punishment from social stimuli, caused by an underlying general breakdown in reward processing.…”
Section: Discussionmentioning
confidence: 99%
“…However, reward learning may be typical in schizophrenia over longer learning trials [410], and in individuals with less severe symptoms [414]. Overall, however, studies of reward learning in individuals with schizophrenia are consistent with the framework that patients with schizophrenia have intact hedonic responses but impaired motivation and reward representation, leading to a failure to motivate their behavior for rewards [415].…”
Section: Reviewmentioning
confidence: 98%